Biochemical quality of cowpea beans grown under water-deficit maintained with hydrogel - Fidelis, Rodrigo Ribeiro; da Silva, Guilherme Sousa; Rauber, Wagner Augusto; Rodrigues, Larissa Urzêdo; Nascimento, Vitor L.; Siebeneichler, Susana Cristine (Revista de Ciencias Agrícolas, 2020)
Investigations related to the effects of the hydrogel use in a water-deficit conditions on the biochemical composition of the harvested products are scarce. The aim of this study was to verify the influence of hydrogel on the biochemical response of cowpea beans produced under water-deficit in southern Tocantins. The experiment was a randomized complete block design with four replications. The treatments were obtained in a 2x5 factorial scheme, being: two sources of hydrogel (Hydroplan-EB HyC and Polim-Agri PP) and five concentrations (0, 5, 10, 15, and 20kg ha-1). After harvesting, the grains of cowpea, BRS Vinagre cultivar, were ground and chemically analyzed. The oil content of the seeds agreed with the reference values. The use of Polim-Agri PP promoted the best levels of amino acids (0.38mg g-1) and proteins (243.22mg g-1) of the grains. The carbohydrate content of them (Ȳ= 81.44mg g-1) was better using Hydroplan-EB HyC, regardless of the concentration applied. The application of 6.28kg ha-1 of Polim-Agri PP provided the highest starch content (842g mg-1). The use of hydrogel improves the biochemical quality of cowpea beans produced under water deficit in southern Tocantins.